2008
DOI: 10.1016/j.physbeh.2007.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Licking for taste solutions by potassium-deprived rats: Specificity and mechanisms

Abstract: There has been little work on the specificity and mechanisms underlying the appetite of potassium (K + ) deprived rats, and there are conflicting results. To investigate the contribution of oral factors to changes in intake induced by K + deficiency, we conducted two experiments using 20-s "brief access" tests. In Experiment 1, K + -deprived rats licked less for water than did replete rats. After adjusting for this difference, K + -deprived rats exhibited increased licking for 100 mM CaCl 2 , 100 mM MgCl 2 , a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
1
6
1
Order By: Relevance
“…In rodents, both sodium (Ferreyra & Chiaraviglio, 1977) and potassium deprivation (Adam & Dawborn, 1972;Tordoff, 1992;Zucker, 1965) increase sodium appetite. However, a more recent study suggests that potassium deprived rats do not have a specific appetite for sodium, but a more general attraction to various minerals measured by licking rates of different kinds of chloride salts (Guenthner, McCaughey, Tordoff, & Baird, 2008). In contrast to animal studies, low levels of both potassium and sodium did not show any effect on human salt taste in the present study.…”
Section: Discussioncontrasting
confidence: 96%
“…In rodents, both sodium (Ferreyra & Chiaraviglio, 1977) and potassium deprivation (Adam & Dawborn, 1972;Tordoff, 1992;Zucker, 1965) increase sodium appetite. However, a more recent study suggests that potassium deprived rats do not have a specific appetite for sodium, but a more general attraction to various minerals measured by licking rates of different kinds of chloride salts (Guenthner, McCaughey, Tordoff, & Baird, 2008). In contrast to animal studies, low levels of both potassium and sodium did not show any effect on human salt taste in the present study.…”
Section: Discussioncontrasting
confidence: 96%
“…The rodent brief-access taste aversion (BATA) model is one of the popular approaches used for taste evaluation [3945]. In this model, rodents such as mice or rats, are mildly water-deprived and then put into as “lickometer” which records the number of “licks” that the rodents make to different concentrations of the compound under test samples presented in several sipper tubes [46].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has been shown that TRPV1 knockout and wild-type mice have equal detection thresholds for NaCl (Ruiz et al 2006;Treesukosol et al 2007). Furthermore, it has been shown that the increased licking responses to NaCl solutions by potassium-deprived rats were unaffected by TRPV1 antagonists, SB-366791 and ruthenium red (Guenthner et al 2008). Behaviorally, amiloride is an excellent antagonist because it is tasteless to rats (Markison and Spector 1995), while TRPV1 antagonists like CPC taste bitter to rats (St. John and Hallagan 2005), and SB-366791, a lipophilic molecule, must be dissolved in DMSO.…”
Section: Response Profiles Of Nacl-specialist and Acid-generalist Neumentioning
confidence: 99%